The tourism sector and its adaptation measures with the requirements of sustainable development and the green economy in Algeria. - Belaidi, Mohamed; Zouache, Zohir (Journal of Human Sciences, 2022)
This study examines in particular Algeria’s need to formulate policies that include tools and objectives for the development of the tourism sector, which has become a major and distinguished role in achieving economic diversification, accumulating foreign currency, and providing jobs for the unemployed, provided that the implementation of these policies takes into account the issue of preserving The elements of the environment, so that this can only be materialized by constantly working to remove all negative factors, which can make the tourism sector a source of disruption of the environmental, economic, social and cultural balance, which also reflects the existence of a relationship of influence and integration between tourism and the green economy and development. Sustainable, which is the relationship that is expressed in the term sustainable tourism development.